2014
DOI: 10.1177/1541931214581453
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Demands of Destination Entry using Google Glass and the Samsung Galaxy S4

Abstract: A driving simulation study assessed the impact of vocally entering an alpha numeric destination into Google Glass relative to voice and touch-entry methods using a handheld Samsung Galaxy S4 smartphone. Driving performance (standard deviation of lateral lane position and longitudinal velocity) and reaction to a light detection response task (DRT) were recorded for a gender-balanced sample of 24 young adult drivers. Task completion time and subjective workload ratings were also measured. Using Google Glass for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 3 publications
4
12
0
Order By: Relevance
“…However, because of technical issues, this study was not able to provide task duration measurement for the secondary texting task, nor did Sawyer et al (2014)'s work provide such data. The only work on Google Glass, which provided task duration, was done by the MIT AgeLab (Beckers et al, 2014). Beckers et al (2014) used a destination entry task and compared Google Glass, smartphone with Samsung S Voice (a voice-based application, similar to Apple's Siri or Google Now), and smartphone with touch interaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, because of technical issues, this study was not able to provide task duration measurement for the secondary texting task, nor did Sawyer et al (2014)'s work provide such data. The only work on Google Glass, which provided task duration, was done by the MIT AgeLab (Beckers et al, 2014). Beckers et al (2014) used a destination entry task and compared Google Glass, smartphone with Samsung S Voice (a voice-based application, similar to Apple's Siri or Google Now), and smartphone with touch interaction.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, interacting with technology through a speech interface allowed better driver performance than manual interaction (Beckers et al, 2014,b;He et al, 2014a,b;Peissner et al, 2011), producing smaller lane deviations, fewer off-road glances, smaller steering variance, and lower cognitive workload (Barón and Green, 2006;Beckers et al, 2014;Owens et al, 2011). In contrast, other studies found no significant benefit to driving performance by using a speech-based interface to replace manual inputs (Ishigami and Klein, 2009).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Will HMD incur the same costs as HDD, or will they be more comparable to HMD? Safety researchers have only recently begun exploring how Google Glass influences driving performance (Beckers, Schreiner, Bertrand, Reimer, Mehler, Munger, & Dobres, 2014;He, Choi, McCarley, Chaparro, & Wang, under review;Sawyer, Finomore, Calvo, & Hancock, 2014). These studies all used a car-following task and did not assess other aspects of driving performance, such as tactical lane changes.…”
Section: Introductionmentioning
confidence: 99%
“…These studies all used a car-following task and did not assess other aspects of driving performance, such as tactical lane changes. Additionally, these studies also majorly focused on the speech-recognition feature of Google Glass (Beckers, et al, 2014;Sawyer, et al, 2014)-and they did not examine the costs of using the HMD of Google Glass. We investigated how reading using the see-through HMD of Google Glass influences driving performance, specifically tactical lane change behaviors.…”
Section: Introductionmentioning
confidence: 99%